ANÁLISE DA QUALIDADE DE VIDA DE TRABALHADORES TÉCNICO- ADMINISTRATIVOS E DE APOIO DA UNIJUÍ - CAMPUS IJUÍ - MARCHI, DIONE D.; STUMM, ENIVA M. F.; DAMBROS, INES T. R.; ROSA, FERSON M. D. (Salão do Conhecimento, 2013)
Resumo